Resonant violence : affect, memory, and activism in post-genocide societies - Whigham, Kerry (Genocide, Political Violence, Human Rights Ser., 2022)
From the Holocaust in Europe to the military dictatorships of Latin America to the enduring violence of settler colonialism around the world, genocide has been a defining experience of far too many societies. In many cases, the damaging legacies of genocide lead to continued violence and social divisions for decades. In others, however, creative responses to this identity-based violence emerge from the grassroots, contributing to widespread social and political transformation. Resonant Violence explores both the enduring impacts of genocidal violence and the varied ways in which states and grassroots collectives respond to and transform this violence through memory practices and grassroots activism. By calling upon lessons from Germany, Poland, Argentina, and the Indigenous United States, Resonant Violence demonstrates how ordinary individuals come together to engage with a violent past to pave the way for a less violent future.